Midrash, Apocrypha, Culture Medium and Development Of Doctrine. Some Facts in Quest Of A Terminology - Mcnamara, Martin (Apocrypha, 1995)
Abstract Midrash has been traditionally regarded as something specifically Jewish and rabbinic, but later as a reality found already in the Hebrew Scriptures and present also in New Testament writings. In this essay the more recent debates regarding the nature of midrash are examined in the larger context of inner-biblical exegesis and against the background of canonical process. Some midrash-type features or techniques are examined and these are seen to be found also in apocryhal and traditional Christian commentary literature. In the light of this there is a consideration of the reflection on the afterlife in Irish apocrypha and Irish theological treatises. Abstract Le Midrash, traditionnellement, a été considéré comme un genre littéraire juif et rabbinique. Plus récemment, sa présence a été repérée déjà dans la Bible hébraïque et maintenant aussi dans le Nouveau Testament. Les récents débats autour de la nature du Midrash sont examinés ici dans le contexte plus large de l'interprétation de la Bible par la Bible et sur l'arrièrefond du processus canonique. Quelques-unes des caractéristiques et des techniques midrashiques sont présentées et analysées aussi comme faisant partie de la littérature apocryphe chrétienne, et de la littérature exégétique patristique. Dans ce cadre, on traitera aussi de la réflexion sur l'au-delà se trouvant dans la littérature apocryphe et théologique irlandaise.